Antibacterial and anti-biofilm activities of Disaspidin BB against Staphylococcus epidermidis - Lan, Shihua; Chen, Xiaofeng; Yin, Chuanping; Xie, Shengjun; Wang, Shuaishuai; Deng, Rongrong; Shen, Zhibin (Frontiers in Microbiology, 2023)
Staphylococcus epidermidis (S. epidermidis, SE) infections are an important concern worldwide, especially with the associated biofilms and drug resistance. Herein, we investigated the inhibitory effect of Disaspidin BB obtained from plant extractions on clinical S. epidermidis strains and their biofilms. Moreover, we preliminarily studied the mechanism of its anti-biofilm activity. The broth dilution method was used to determine the minimum inhibitory concentrations (MIC) of Disaspidin BB on 11 clinical S. epidermidis strains (MIC value of 0.63 ~2.5 µg/mL). SE-05 was found to be erythromycin-resistant (MIC value > 8 μg/mL) and Disaspidin BB sensitive (MIC value of 0.63 μg/mL). The time-kill curve assay indicated that Disaspidin BB showed antibacterial activity against SE-05 at different growth stages. The metabolic activity and total biomass of drug-treated SE-05 biofilms at each stage were significantly scavenged as determined by crystalline violet and XTT assays, and the scavenging effect of Disaspidin BB on SE-05 biofilm was also confirmed by SEM observation. The results of real-time quantitative PCR showed that subinhibitory concentrations of Disaspidin BB could inhibit biofilm formation by regulating the expression of key genes (aap, atlE, icaA, luxS, recA) in SE-05 biofilm formation. In addition, expression of polysaccharides, proteins, and extracellular DNA in the biofilm matrix after the intervention of Disaspidin BB was significantly reduced, and it was tentatively determined that the ability of SE-05 biofilm formation and its stability were thus disturbed. This study showed that Disaspidin BB has a promising antibacterial effect on erythromycin-resistant S. epidermidis and a significant scavenging effect on its biofilm. This provides a theoretical basis for the further development of BB as a new drug for the treatment of skin infections caused by S. epidermidis.